Franske adjektivisk afledte adverbier, der tager præpositionssyntagmer indledt med præpositionen à som argumenter: En valensgrammatisk undersøgelse - Annemette Skot-Hansen (Copenhagen Business School (CBS), 2009)
– The purpose of this dissertation is to map the valency structure of a subset of the French adverbs. More specifically, the dissertation seeks to answer the following questions: What valency structure follows from the lexical content of the adverbs investigated? What is the nature of the semantic relation established? What is the status of the valents relative to the adverb and relative to other valents? The empirical object of investigation is focused on adverbs derived from adjectives which take prepositional phrases headed by the preposition à as their complement. In addition, the delimitation chosen for this dissertation is a class of adverbs which share the feature that they carry the suffix -ment, which developed from the Latin noun mens, meaning “spirit/thought/mood/tenor”. It is argued that the fusion of an adverb and mens establishes the general meaning [in an adjective spirit/thought/mood/tenor], i.e. the adverb retains the general quality denoted by the adjective, but the meaning targets the verb situation (at clause level) or the quality (at phrasal level) which saturates the argument of the adverb. Following tradition, the analysis adopted here, takes the verb situation to be realised by the predicate, and the quality to be realised by an adjective phrase, which may be realised by a past participle or, in rare cases, by another adverb. Since the valent is required by the lexical content of the adverb, it is assumed, following Herslund and Sørensen, that the valent is a fundamental valent. Another important feature of the adverbs which are analysed in this dissertation is that they establish a relation between two entities. This means that in addition to its fundamental valent, the adverb takes a further valent which it links with the fundamental valent. This second valent is referred to as the second valent of the adverb. The two valents are analysed as two relata in a relation. Unlike the fundamental valent, the second valent is always at phrasal level. When the adverb functions at clausal level, the second valent is realised as the prepositional object of the preposition phrase headed by à. This realisation is, however, not possible when the adverb functions at phrasal level. It is argued that this is a consequence of the fact that it is impossible to insert other constituents between the adverb and the adjective, adverb or participle which is modified by the adverb. The result is that where the second valent is realised, the adverb moves from preposition to postposition relative to its fundamental valent. In the data investigated the second valent denotes very different entities such as situations denoted by verbs and qualities, but also objects and abstract entities. The individual adverbs which are investigated here each determine their valency. In general there are different sources that allow us to uncover the core meaning of a word. The sources chosen in this dissertation are: the semantic roles assigned by the adverbs, their symmetry, elements of shared semantics or partial synonymy, their morphology and etymological roots. In order to bring together these different sources, the dissertation postulates a denotation design for each adverb. The etymology of the adverbs has been a particularly helpful in determining the relation and valency they establish. In addition to adverb and adjective suffixes, the majority of the adverbs investigated have a preposition in their synchronic morphological make-up which denotes a relation between two entities: some adverbs contain both a preposition and a morpheme from another word class, e.g. comparativement and subséquemment, while others contain only a preposition, e.g. antérieurement and postérieurement. A very small subset does not contain a preposition, but only a single adverb morpheme which denotes the relation in question, so, for instance, the adjectives par and similis, which have formed pareillement and semblablement, denote a relation between two relata. From an etymological perspective, a few adverbs, such as latéralement, do not denote a relation – so it is only through the formal realisation of the preposition phrase that the relation is established. The dissertation maps the etymological and morphological structure of the adverb and the range of functions that the adverb and its valents can have at clausal and phrasal level. The function of the adverb is relevant to the extent that the function affects its semantics and its valency structure. The effect of function is seen in some adverbs when they operate on clausal or on phrasal level and in other adverbs when they modify entire clauses or just the verb.
hdl:10398/7944
Keywords: 650